Pengaruh Tingkat Kesiapan Dan pemahaman Pelaku UMKM Terhadap Implementasi Laporan Keuangan Berbasis SAK EMKM - Suci Rahmaddani Sadri; Gustati, Gustati; Handayani, Desi (Journal of Applied Accounting And Business, 2024)
This study aims to analyze the effect of the level of readiness and accounting understanding of MSME actors on the implementation of financial statements based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This research uses quantitative methods with a descriptive approach. Data collected through questionnaires distributed to 64 embroidery and embroidery MSMEs in North Pariaman District. The selection of this location was based on the fact that North Pariaman Subdistrict has a concentration of MSMEs in the embroidery and gold thread embroidery sectors, which are the superior products of this region. In addition, MSMEs in this region show significant economic potential, but have not fully adopted appropriate accounting standards, such as SAK EMKM. The analysis technique used is multiple linear regression. The results of this study indicate that the level of readiness and understanding of MSME actors has a significant positive effect on the implementation of SAK EMKM. Thus, the better the readiness and understanding of MSME actors, the more effective the implementation of SAK EMKM-based financial statements. This research makes an important contribution to efforts to encourage MSMEs to adopt better accounting standards to improve the transparency and accuracy of financial statements.